Peran Aktif NGO Humana dalam Memfasilitasi Pendidikan Anak-Anak Tenaga Kerja Indonesia (TKI) di Sabah Malaysia - Muhammad Muyamin (Universitas Diponegoro, 2019)
This paper explains why Humana, as a Non-Governmental Organization (NGO), provides education to children from Indonesian Migrant Workers (TKI) in Sabah Malaysia. Humana as an NGO in Malaysia has been provided education for marginalized children in Sabah. In fact, Indonesia has given attention to the education of TKI’s children in Sabah. However, Humana continues to provide education services to TKI’s children in Sabah. Humana has a reason to keep up on this issue. This paper collects data from the Indonesian government, including Indonesian Embassy in Malaysia, and the NGO Humana. This paper finds that Humana has a basic idea that encourages targets and goals which in turn provides education for TKI’s children in Sabah.